A Conceptual Model for the Development of Transmodern Innovations - Aleksandr Borzov (Sustainable Development and Engineering Economics, 2024)
Innovation processes are strongly influenced by changes in economic, political, technological and other external factors. For instance, economic instability and political uncertainty can both stimulate and limit innovative activity in organisations. Transmodern innovation is a concept that involves scientific and technological advancements that may remain unutilised until favourable changes occur in technological or economic conditions. The purpose of this study is to develop a conceptual model for transmodern innovation that takes into account the dynamics of innovation, including the intensity, economic prerequisites, external changes and degree of innovation adaptation. This model will help organisations to better understand and respond to the complexities of the innovation process. The resulting model is a comprehensive tool for analysing changes in innovation activity and the external environment over different time phases, including the initial state (t0), the transition to new conditions (t1) and the final state (tx). In this model, the ‘Final stage of tx’ block represents the final stage, which allows us to draw conclusions about the success of adaptation and innovation development. This is the basis for formulating strategic conclusions and recommendations for future development.